Da promessa à realidade: a cidade potiguar do século XIX, a partir do olhar da elite - Borba, Adriana Carla de Azevedo (2014)
The purpose of this research is to apprehend the perception that the ruling elite, especially the Presidents of the province of Rio Grande do Norte/Brazil, had about the potiguar city, that is, the urban localities existing in the province along the 19th century. By interweaving political, administrative, socioeconomic and spatial aspects, the study of this perception involves two distinct moments, which are also linked: a moment of apprehension of the city, that is, how the elite seizes, describes and criticizes the city; and, a second moment, which occurs simultaneously or after the first moment, of intervention in the city, in which the elite exposes its vision and projects for the city and for the territory. Rather than describing the potiguar city in itself, the research is an attempt to reveal how it was perceived along this process from a particular standpoint or discourse, official and elitist, which did not correspond necessarily or completely to what it was in reality. We tried to understand, always through the lens of the discourse, how the ruling elite perceived the potiguar city based on what their members thought about other urban realities, particularly of the advanced countries; how, within an integrated vision, this city was characterized in political, administrative, socioeconomic and spatial terms and how it consolidated itself along the period established for the research. Qualitative and historical in nature, this study was also methodologically developed based upon bibliographical and documental research. Given the fact that this research works with descriptions, comparisons and interpretations, it was necessary to make use of tools such as the discourse analysis in order to apprehend, as much as possible, what lay behind the words of the elite. The primary sources used were essentially the official documents produced by the Presidents of the province, as well as other documents written by top government officials and other members of the administration staff, all of them composing the so-called ruling elite of Rio Grande do Norte. Secondary sources were books and other publications, theses and dissertations, among others. The research made possible the identification of a certain perception of the potiguar city in the 19th century, which is certainly limited because it is grounded on a specific discourse - that of the political and administrative elite, but which, in spite of such a limitation, is still useful to understand the city and its evolution along the period established, among other noteworthy remarks